The Correlation between Cognitive Diversity and EFL Learners' Speaking Ability - Dhari, Adwitya Widya; Syafryadin, Syafryadin; Sukesi, Erni (Journal of English Education and Teaching, 2024)
Speaking ability among English as a foreign language learners (EFL) is influenced by various factors, including cognitive diversity that encompasses individual differences in cognitive styles, information processing, problem-solving approaches, and learning preferences. This study investigated the relationship between cognitive diversity and speaking abilities among English Education students at the University of Bengkulu. Using a quantitative correlational approach with 30 students, cognitive diversity was measured through a questionnaire, and speaking ability was assessed via oral presentations. The data analysis involved calculating Simpson's Diversity Index to measure cognitive diversity levels, Cohen's Kappa to assess the inter-rater agreement on speaking ability scores, and Pearson's correlation analysis to determine the relationship between cognitive diversity and speaking ability. Findings revealed a positive but weak correlation (r=0.244, p=0.193) between the variables. While aligning with some prior research on individual cognitive differences in language acquisition, the modest correlation contradicts other findings on cognitive styles' influence on speaking ability among EFL learners. This dissimilarity may arise from sample size, student population characteristics, and other factors like instructional approaches and affective variables. The study emphasizes the importance of taking cognitive diversity into account, along with other factors, to optimize holistic development in EFL-speaking.